2018
DOI: 10.1177/0030727018766956
|View full text |Cite
|
Sign up to set email alerts
|

Identifying opportunities for value chain development in the Kenyan coffee sector

Abstract: By developing a model that describes the Kenyan coffee value chain, this study evaluates opportunities emanating from four scenarios representing productivity gains in the various value chain stages of the coffee sector and additional three scenarios reflecting shifts in market situations. Results show that productivity-enhancing policies have stronger effects on coffee output and export performance if they target the milling stage of the value chain. Export subsidy and favourable external marketing conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Unexpectedly in our study findings, the results indicated positive relationship between cost of transportation and quantity of coffee produced. One unit increased to cost of transport, the expected quantity of coffee production shifted to 0.75 percent of coffee and our findings are similar to the results of Aragie (2018) in their study on identification of opportunities for value chain development in the Kenyan coffee sector by adoption of a modeling approach. The results in table 1 also indicated that distance from farm to nearest road was statistically significant the marketing factor affecting the marketed coffee production at 5% level of significance.…”
Section: IVsupporting
confidence: 89%
“…Unexpectedly in our study findings, the results indicated positive relationship between cost of transportation and quantity of coffee produced. One unit increased to cost of transport, the expected quantity of coffee production shifted to 0.75 percent of coffee and our findings are similar to the results of Aragie (2018) in their study on identification of opportunities for value chain development in the Kenyan coffee sector by adoption of a modeling approach. The results in table 1 also indicated that distance from farm to nearest road was statistically significant the marketing factor affecting the marketed coffee production at 5% level of significance.…”
Section: IVsupporting
confidence: 89%